A thermochemical heat storage system for households: Thermal transfers coupled to chemical reaction investigations - Fopah Lele, Armand (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2015)
Heating is most important part of thermal energy demand, and accounts for large amounts ofenergy consumption in cold regions. Renewable energy sources will be of great importance inorder to cover future energy demands. However, their intermittency is rightly considered asinconvenient. Thus, a more effective management of demand, coupled with efficient storagesystems is required. Based on this perception, thermal systems coupled with electricityproduction have been efficiently designed, they are the so called “combined heat and power”(micro-CHP). Nonetheless, heat losses from the thermal part of their system lead to electricityfluctuation. Therefore, the use of micro-CHP in combination with a volume-efficient and nearlylossless heat storage system to counteract electricity fluctuations is a viable solution.The heat storage system in this work is based on reversible thermochemical reactions, suchas dehydration and hydration of inorganic salts, which exhibits very high energy density (up to628 kWh·m-3 of storage material). The chosen inorganic salt (SrBr2·6H2O) reacting with purewater vapour operates within a closed system. The objective of this work is to design a systemthat thermodynamically matches the combination with micro-CHP. Therefore, investigationshave been performed from the material at micro-scale to the system at lab-scale. Models weredeveloped on the basis of heat and mass transfer with chemical reaction and were done in orderto numerically analyse the system. Experiments were additionally performed to consolidate thenumerical tools for future studies. Characterization experiments have been designed and tested.Thermo-physical properties (thermal conductivity, specific heat capacity, permeability, chemicalkinetics) of the reactive salt were then determined to be used as parameters into the sodeveloped models.The numerical simulations lead to the time-space evolution of heating fluid, reactive bedtemperatures and reactor pressure. The originality of this study is to model the coupled heat andmass transfer with chemical reaction on a 3D geometry to be close to the reality. Results help tonumerically and experimentally analyse the thermochemical heat storage performances. Thebed energy density is experimentally found to be 531 kWh·m-3 of salt hydrate. Based on thecondensation temperature during the experimentation, a reactor energy density of 140 kWh·m-3and a storage capacity of 65 kWh with a thermal efficiency of 0.78 are obtained. This systemproves the recovery capacity of more than 2/3 of the input energy. Various aspects of design andrecommendation for optimisation aspect that could help during prototype development aretaken into account and addressed. Comparison simulation-experiment is then performed anddiscussed, showing encouraging results, even if limited at lab-scale.
Ein thermochemischer Wärmespeicher für Haushalte: Untersuchungen von Thermotransfers mit chemischen Reaktionen
Keywords: Thermal Energy Storage; Energy Efficiency; Wärmespeicher; Energieeffizienz; 333.7 Natürliche Ressourcen, Energie und Umwelt